2015
DOI: 10.1039/c5sc00794a
|View full text |Cite
|
Sign up to set email alerts
|

Unified total synthesis of the natural products endiandric acid A, kingianic acid E, and kingianins A, D, and F

Abstract: A measure of the strength of a synthetic strategy is its versatility: specifically, whether it allows structurally distinct targets to be prepared. This work describes the total synthesis of natural products of three distinct structural types from a common intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“… 503 , 516 , 521 A related radical cation Diels–Alder approach has also been utilized in the synthesis of (±)-kingianic acid E ( 639 ) ( Scheme 110 ). 522 …”
Section: Visible-light Photoredox Catalysis—single-electron Transfer mentioning
confidence: 99%
“… 503 , 516 , 521 A related radical cation Diels–Alder approach has also been utilized in the synthesis of (±)-kingianic acid E ( 639 ) ( Scheme 110 ). 522 …”
Section: Visible-light Photoredox Catalysis—single-electron Transfer mentioning
confidence: 99%
“…More recently, Sherburn and coworkers demonstrated that (Z,Z,Z,Z)-tetraenes can also undergo the pericyclic cascade to produce endiandric acids, though only at elevated temperatures. [9][10][11] The impressive biomimetic syntheses by Nicolaou and Sherburn relied upon cis-selective reductions of conjugated alkynes (diynes or tetraynes) to generate octatetraene intermediates and trigger 8π/6π electrocyclization cascades. We sought to develop a concise and modular approach to endiandric acid derivatives with both fused and bridged tetracycles by exploring an alternate route to the 8π/6π electrocyclization cascade.…”
Section: Introductionmentioning
confidence: 99%
“…[116] Unfortunately, direct lithation of TMS protected precursor 358 led to decomposition. [116] Unfortunately, direct lithation of TMS protected precursor 358 led to decomposition.…”
Section: Transformations Of Terminal and Trialkylsilyl Protected Polymentioning
confidence: 99%